DARE Newsletter, Vol. 3, Nos. 2/3, Spring/Summer 2000 - DARE; Attig, Catherine R.; Blake, Elizabeth; Gardner, Elizabeth R.; Hall, Joan Houston; Kolstad, Sheila Y.; Shuy, Roger W.; Simon, David; von Schneidemesser, Luanne; Zwilling, Leonard (Dictionary of American Regional English, 2000)
Contents: "Frederic G. Cassidy"; "Funding Update" by David Simon; "Ask a Fieldworker"; "Notes and Quotes"; "DARE Staffers Remember Fred Cassidy" by Joan Houston Hall, Elizabeth R. Gardner, Leonard Zwilling, Sheila Y. Kolstad, Elizabeth Blake, Luanne von Schneidemesser, and Catherine R. Attig; "A Colleague Remembers" by Roger W. Shuy; "Coming in Volume IV"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Fieldwork; Lexicography; Regional English; English Language--Dialects--United States